A comparative study for the stabilisation of heavy metal contaminated sediment by limestone, MnO sub(2) and natural zeolite - Yi, Yuanjie; Wen, Jia; Zeng, Guangming; Zhang, Taotao; Huang, Fenghu; Qin, Haiyan; Tian, Shiyu (Environmental science and pollution research international, 2017)
Three amendments including limestone, MnO sub(2) and natural zeolite were assessed for their stabilisation effects on Zn, Cu, Pb and Cd in sediment of east Dongting Lake, mid-south China. The metals were first subject to pollution status and potential ecological risk assessment to identify the current and potential hazards to ecology. Speciation of the metals in the sediment treated with amendments was then carried out by BCR sequential extraction procedure in order to evaluate metal contents and their potential mobility. The total concentrations of Zn, Cu, Pb and Cd in the east Dongting Lake were all above the means of national stream sediment and soil guidelines. The sediments were currently unpolluted to moderately pollute with Zn, Cu and Pb and strongly polluted with Cd. Zinc, Cu and Pb posed low risks to the lake ecosystem, and Cd had the highest potential risk that caused the overall risk of the sediment to be high or very high. Limestone stabilised Cu and Zn effectively, yet mobilisation of Cd and Pb by such amendment was also observed. MnO sub(2) effectively reduced the extractable Cd and Pb. The effect of natural zeolite on metal stabilisation in the sediment was least notable. Limestone and MnO sub(2) showed higher metal stabilisation efficiencies than zeolite. However, a single amendment is unable to achieve the goal of stabilisation for all metals. A combination use of the advantageous amendments or a search of a stronger stabiliser should be the interest of our future study.